How antiretroviral data cleaning reshaped Mozambique’s progress to reaching HIV epidemic control - Aleny Couto; Orrin Tiberi; Lindsay Templin; Morais da Cunha; Jose R. Mondlane; Jose Mizela; Hermínio Nhaguiombe; Ryan Keating; Ferreira Ferreira; Emilton Cumbana; Irénio Gaspar (PLoS ONE, 2026)
Quality data is fundamental for any public health program, especially for long-term care programs that rely on longitudinal data for decision making. In Mozambique, there had been a growing discrepancy between the number of people living with HIV (PLHIV) on antiretroviral treatment (ART) reported in the national system when compared to pharmacy and electronic medical records. A national ART data cleaning exercise was conducted in the first semester of 2024 to improve the accuracy and reliability of the nationally reported data. All health facilities with ART services (n = 1,757) compared their nationally reported data between the clinical data available at the health facility and the pharmacy medication pick-up data. The records that were successfully validated were marked as active, while the others were non-active. Upon completion of the review, the nationally reported data were revised. There was a 9.9% decrease (2,166,941–1,951,724) in the number of PLHIV considered currently on ART between December 2023 and June 2024. Among age groups, there was a 28.7% decrease among those less than 10 years of age, 26.4% among those between 10 and 19 years, and 8.0% for those 20 years or more. Cabo Delgado was the province with the largest percentage difference (21.1%, −28,799 PLHIV currently on treatment), while Zambezia had the largest absolute decline, of 41,445 (−8.9%). The notable decreases in PLHIV on ART resulted in an increase in Mozambique’s estimates for new infections, AIDS-related deaths, and vertical transmission. These updates allowed for a more realistic understanding of the HIV epidemic in Mozambique, including highlighting provinces with large data quality issues evidenced by substantial changes in PLHIV on ART numbers. This activity highlighted challenges that exist in paper-based reporting systems and provides evidence for a renewed focus on improving data quality for decision making.